Mrs. Frisby and the rats of Nimh - O'Brien, Robert C.; Bernstein, Zena (New York Aladdin Books, 1986)
Having no one to help her with her problems, a widowed mouse visits the rats whose former imprisonment in a laboratory made them wise and long lived.
Keywords: Mice -- Fiction; Rats -- Fiction